Pemberian Layanan Bimbingan Pribadi Sosial Untuk Meningkatkan Self Esteem Siswa - Arifin Nur Budiono; Qomariatul Laily (FKIP Universitas Islam Jember, 2018)
Self esteem can occur in adolescence, one of which is at school age. School age is the transition period of individuals from childhood to adulthood, so that many problems are faced, both with oneself and with the surrounding environment. This study aims to determine the increase in student self esteem by providing personal social guidance services. This study used guidance and counseling action research (PTBK). The population is determined as the research respondents. The data collection methods used in this study were questionnaire method, and observation. Based on the results of the study; the first cycle at the first meeting, the respondents still showed low self esteem, which showed only 50%. While in cycle 2, researchers emphasized more on providing reinforcement to respondents so that the self esteem can increase to 70%. This can be seen from the column showing that self esteem has increased to 70%. Keywords: self esteem, social personal guidance